Tax Payment Revenue Ratio as Tax Risk Analysis for Manufacture Industry in Indonesia after Tax Amnesty Policy - Muhammad Rifky Santoso; Erlina Erlina (International Journal of Applied Business and International Management, 2020)
Indonesia’s Tax Amnesty potentially will increase state tax revenues in rupiah; however, it cannot increase tax compliance as measured by the tax ratio value. Tax audit as a law enforcement needs to be carried out on taxpayers with high risk in utilizing tax amnesty policies for tax avoidance. By comparing the ratio of tax payment revenue (TPR) in manufacturing companies listed on IDX, this study finds that most of the samples are indicated to have a high risk of tax avoidance, since the value of TPR is significantly lower when the tax amnesty is enacted, compared to that prior to the enactment. To determine which taxpayers are doing illegal tax avoidance and need to be audited, further analysis is necessary for those with significant TPR reduction, one of which is by analyzing the financial ratios. This method is possibly used for each industry due to its different characteristics. It facilitates both the tax authority to increase taxpayer compliance and the taxpayer to make tax planning.